2008
DOI: 10.1302/0301-620x.90b10.20533
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between inclination of the acetabular component and metal ion levels in metal-on-metal hip resurfacing replacement

Abstract: We examined the relationships between the serum levels of chromium and cobalt ions and the inclination angle of the acetabular component and the level of activity in 214 patients implanted with a metal-on-metal resurfacing hip replacement. Each patient had a single resurfacing and no other metal in their body. All serum measurements were performed at a minimum of one year after operation. The inclination of the acetabular component was considered to be steep if the abduction angle was greater than 55 degrees. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

29
341
5
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 457 publications
(376 citation statements)
references
References 40 publications
29
341
5
1
Order By: Relevance
“…This was unexpected given that the literature suggests that steep cup inclination is associated with increased release of metal wear debris [7,27,30,31] and increased wear is associated with pseudotumor formation [15,22]. However, there is some recent evidence of high rates of devastating soft tissue reactions in patients with well-positioned MOM hip prostheses [8], which supports our findings.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This was unexpected given that the literature suggests that steep cup inclination is associated with increased release of metal wear debris [7,27,30,31] and increased wear is associated with pseudotumor formation [15,22]. However, there is some recent evidence of high rates of devastating soft tissue reactions in patients with well-positioned MOM hip prostheses [8], which supports our findings.…”
Section: Discussionsupporting
confidence: 85%
“…Retrieval studies of current-generation MOM hips have suggested edge loading, resulting from adverse cup orientation, leads to a higher wear of the components and raised blood metal ion levels [7,27,30,32]. In vivo studies have suggested disparities in certain design features, such as the clearance [41] and arc of cover [27], are important factors affecting component wear rates and the risk of edge loading.…”
Section: Introductionmentioning
confidence: 99%
“…The component positioning parameters most strongly associated with a low early complication rate and high survivorship long-term include acetabular component inclination and femoral stem shaft angle [19,22,23,31,37,38,43,47]. Therefore, we used these measures to determine the learning curves.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that notching of the femoral neck, exposed cancellous bone, and varus placement of the femoral component increase the likelihood of femoral neck fracture [5,9,27,36,43]. Numerous studies demonstrate cup inclination or abduction angle greater than 50°to 55°is associated with high levels of serum metal ions and higher rates of early failure [19,22,23,31]. Therefore, accurate component placement is critical to avoid complications after hip resurfacing.…”
mentioning
confidence: 99%
“…Previously, a few studies were directed at proper femoral component stem orientation in HRA [19,26,27]. However, it now appears proper placement of the acetabular component may be even more critical to the success of this procedure [8,9,11,21,30]. We investigated the value of using a single intraoperative portable crosstable AP radiograph to improve the accuracy of placing the acetabular component within a target range of inclination.…”
Section: Discussionmentioning
confidence: 99%